PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAK PESERTA DIDIK DI MADRASAH IBTIDAIYAH HAQQUL YAQIN LEMPASING KABUPATEN PESAWARAN TAHUN PELAJARAN 2021/2022 - Dahlia, Dahlia; Handoko, Cipto; Feriyansyah, Feriyansyah (UNISAN JURNAL, 2023)
The focus of research in this writing is (1) How is the method of fostering students’ akhlakul karimah through religious activities at Madrasah Ibtidaiyah Haqqul Yaqin Lempasing? (2) How is the evaluation of the moral development of students through religious activities at Madrasah Ibtidaiyah Haqqul Yaqin Lempasing? (3) What are the supporting and inhibiting factors for the implementation of the moral development of students through religious activities? The objectives of this research are 1. To find out the methods of implementing the akhlakul karimah development of students through religious activities, 2. To know the evaluation of the implementation of the akhlakul karimah fostering of students through religious activities, 3. To know the supporting and inhibiting factors of the implementation of the moral development of students through activities religious. The results of the research show that the role of PAI teachers in fostering the morals of students can be seen from the methods used, including 1) Habituation by carrying out Dhuha and Dhuhur prayers in congregation regularly every day. Mauidzah or Ibrah. This method of advice is given during cult activities or lectures delivered by teachers who have been scheduled by the school. 2) Mauidzah or Ibrah. This method of advice is given during cult activities or lectures delivered by teachers who have been scheduled by the school. 3) Supervisory Method 4) Method of Sanctions. Evaluation of Students’ Akhlakul Karimah Development Through Religious Activities at Madrasah Ibtidaiyah Haqqul Yaqin Lempasing